Growth of Black Orchids (Coelogyne Pandurata Lindl) with Additional Ecoenzyme Liquid Organic Fertilizer and Biostimulant of Cengkodok Leaf Extract - Zulfa Zakiah; Masnur Turnip (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Acclimatization of black orchid plantlets (Coleogyne pandurata Lindl.) with cengkodok leaf extract biostimulant treatment has been successfully carried out, but still have slow growth. To support growth and development at the enlargement stage, cultivated orchids need to be given eco enzyme liquid organic fertilizer (LOF) derived from various sources of organic matter. Provision of ecoenzyme LOF combined with biostimulant 20 mg/l of Cengkodok leaf extract to increase the efficiency of nutrient absorption. The aim of the research was to find the best type and concentration of LOF for the growth of black orchids at the enlargement stage. The study used a Complete Randomized Design (CRD) with two treatment factors namely type of LOF (ecoenzyme (ee) LOF from vegetable and fruit waste, ee LOF from pineapple peel waste, and